2021
DOI: 10.1002/hbm.25622
|View full text |Cite
|
Sign up to set email alerts
|

Influence of layered skull modeling on the frequency sensitivity and target accuracy in simulations of transcranial current stimulation

Abstract: With the development of electrical stimulation technology, especially the emergence of temporally interfering (TI) stimulation, it is necessary to discuss the influence of current frequency on stimulation intensity. Accurate skull modeling is important for transcranial current stimulation (tCS) simulation prediction because of its large role in dispersing current. In this study, we simulated different frequencies of transcranial alternating current stimulation (tACS) and TI stimulation in single‐layer and laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Important foundational research comparing E-field modeling estimates and actual intracranial recordings established a strong linear relationship between these values, mitigating some but not all of the concern that E-field modeling is an estimation of cortical stimulation 58 , 59 . Further improvements in E-field modeling methodology, such as taking different sub-layers of meninges 60 , skull composition 61 , or anisotropy 62 into consideration, may help to further refine the fidelity of E-field models. A further limitation is that we combined relative (i.e., 10–10 EEG-based electrode placements) and absolute measurements (i.e., 2 cm increments further apart), which resulted in slight disparities of up to a few millimeters between inter-electrode distances between participants.…”
Section: Discussionmentioning
confidence: 99%
“…Important foundational research comparing E-field modeling estimates and actual intracranial recordings established a strong linear relationship between these values, mitigating some but not all of the concern that E-field modeling is an estimation of cortical stimulation 58 , 59 . Further improvements in E-field modeling methodology, such as taking different sub-layers of meninges 60 , skull composition 61 , or anisotropy 62 into consideration, may help to further refine the fidelity of E-field models. A further limitation is that we combined relative (i.e., 10–10 EEG-based electrode placements) and absolute measurements (i.e., 2 cm increments further apart), which resulted in slight disparities of up to a few millimeters between inter-electrode distances between participants.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2017, Grossman et al brought TI-tACS into the field of brain stimulation [ 3 ], and many subsequent studies have shown evidence supporting its effectiveness [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, to the best of our knowledge, this is the first study to test the safety of TI-tACS in the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the intersection of the two currents, there would form an envelope at a low-frequency equal to the difference of the two high-frequency currents (e.g., 20 Hz), which can modulate deep brain areas like conventional tACS ( Figure 1 ) [ 4 , 5 ]. Although the results of subsequent animal studies [ 6 , 7 , 8 ], simulation studies [ 9 , 10 , 11 , 12 , 13 , 14 ] and human studies [ 15 , 16 ] supported the effectiveness of TI-tACS in stimulating brain areas in a selective manner, its safety in stimulating human brains is still unclear. It is necessary to verify the safety of TI-tACS before we apply TI-tACS to human participants and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in the 1980s, this method has been used to improve a variety of diseases, such as mood [ 89 ], cognitive [ 90 ], and motor disorders [ 91 ]. It is generally accepted that TES can alter cortical excitability, for example, anodal stimulation has an excitatory effect, cathodal stimulation has an inhibitory effect, and alternating current can modulate endogenous brain oscillations [ 92 , 93 ]. Accumulating evidence suggested that non-invasive TES could affect inflammatory response and microglial function.…”
Section: Neuromodulation Therapy Reduces Cytokines Production and Imp...mentioning
confidence: 99%